Simulation of Train Scheduling and Evaluation of Passenger Level of Service : A Case Study of Mass Rapid Transit Blue Line: A Case Study of Mass Rapid Transit Blue Line - Machoo, Kanticha; ภักดิ์แจ่มใส จิรภัทร; งามโขนง ชยุตม์; แสงเพชรงาม บุญชัย (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 28, 2023)